Management of Covid-19 among Patients with Comorbid Cardiovascular Disease: A Scoping Review for Decreasing Mortality and Morbidity - Aan Nur'aeni; Hardianti Azhari Putri; Amalina Fildzah Fujilestari; Via Komalasari; Yulpiana Arunita; Atin Janatin; Lintang Tyas Ananda Riani Suara; Firdha Rizkiani Cipta Pertiwi (Universitas Padjadjaran, 2021)
Cardiovascular disease is comorbid with many Covid-19 patients, with Case Fatality Rate (CFR) reaching 10.5%. The efforts made to reduce mortality and morbidity in Covid-19 patients with cardiovascular concomitant diseases are still being executed. This review aimed to identify the interventions and their relation to mortality and morbidity in these patients. This study is s scoping review, with databases used including Ebscohost, Goggle Scholar, Pubmed, and Proquest. This study using inclusion criteria: full-text and written in English. It is using the keywords Cardiovascular disease, Covid-19, and Pharmacotherapy. Articles obtained totaling 145,680. Articles were sorted according to various restrictions, and various inclusion criteria obtained 18 articles. Several treatments can be used to reduce mortality in Covid-19 patients with CVD, they are: the administration of pharmacological drugs such as ACEI, ARB, RAAS inhibitors, and Hydroxychloroquine, statin, and advance cardiogenic shock treatment (MCS, V-A ECMO, and Impella). It discovered some effective treatments in lowering mortality rates. However, these results do not demonstrate consistency. So it is necessary to do more research. In addition, nurses need to develop nursing therapies that can synergize with medical therapies in improving the efficacy of treatment and lower mortality and morbidity in patients.